2012
DOI: 10.1111/j.1742-4658.2012.08560.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and physical linkage between calpains and penta‐EF‐hand Ca2+‐binding proteins

Abstract: The name calpain was historically given to a protease that is activated by Ca2+ and whose primary structure contains a Ca2+‐binding penta‐EF‐hand (PEF) as well as a calpain cysteine protease (CysPc) domain and a C2‐domain‐like (C2L) domain. In the human genome, CysPc domains are found in 15 genes, but only nine of them encode PEF domains. Fungi and budding yeasts have calpain‐like sequences that lack the PEF domain, and each protein (designated PalB and Rim13, respectively) is orthologous to human calpain‐7, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 49 publications
0
32
0
2
Order By: Relevance
“…This promotes the release of virion particles (9) with the help of AAA-ATPase VPS4B (vacuolar protein sorting 4 homolog B) (10,11). The penta-EF-hand protein ALG-2 (apoptosis-linked gene-2, also known as PDCD6) participates in the process by interacting with both ALIX (12,13) and TSG101 (14) in a calcium-dependent manner and bridges ESCRT-III and ESCRT-I through dimerization (15)(16)(17). However, the function of ALG-2 in viral replication, especially that of HIV-1, remains unknown.…”
mentioning
confidence: 99%
“…This promotes the release of virion particles (9) with the help of AAA-ATPase VPS4B (vacuolar protein sorting 4 homolog B) (10,11). The penta-EF-hand protein ALG-2 (apoptosis-linked gene-2, also known as PDCD6) participates in the process by interacting with both ALIX (12,13) and TSG101 (14) in a calcium-dependent manner and bridges ESCRT-III and ESCRT-I through dimerization (15)(16)(17). However, the function of ALG-2 in viral replication, especially that of HIV-1, remains unknown.…”
mentioning
confidence: 99%
“…Recently solved structures, e.g. that of the protease calpain (20), have indicated that the functional motifs of these proteins occur in pairs, either by homodimerization or by heterodimerization, whereas the non-functional fifth EF-hand acts as a dimerization domain.…”
Section: Calcium Binding and Sensor Proteins The Ef-handmentioning
confidence: 99%
“…1,2) Although ALG-2 was originally identified as a pro-apoptotic protein in Tcell hybridoma, 3) ALG-2 knockout mice developed normally with no obvious abnormalities in the immune system. 4) Nonetheless, accumulating data suggest the involvement of ALG-2 in apoptosis, cell cycle, signal transduction, and cancer.…”
Section: Alg-2 Is An Ef-hand-type Camentioning
confidence: 99%